HERITAGE AT THE CROSSROADS OF GEOGRAPHY AND DEVELOPMENT: CASE STUDIES FROM LAHAT REGENCY - Listen Prima; Yanto (Center for Scientific Publication, 2025)
This research investigates the intersection between geography, urban development, and heritage preservation in Lahat Regency, South Sumatra, Indonesia, using Lubuk Sepang and Bangke villages as case studies. Lubuk Sepang's river proximity and Bangke's mountainous terrain distinctly influence settlement patterns, heritage conservation challenges, and developmental pressures. Employing a mixed-methods approach—including fieldwork, geospatial mapping—the study identifies how geographical features impact heritage sites, community dynamics, and conservation strategies amid rapid urbanization. The findings highlight that settlements near rivers face threats from infrastructure expansion, erosion, and environmental degradation, risking loss of cultural heritage linked closely to water resources. In contrast, mountainous settlements struggle with deforestation, landslides, and infrastructural encroachment, threatening ecological integrity and traditional heritage. Effective heritage conservation necessitates integrating geographical considerations into urban planning, adopting technological innovations such as GIS (Geographic Information System) and digital archiving, and fostering active community participation. The study provides actionable recommendations to harmonize urban growth and heritage preservation in geographically diverse areas.